Faktor-Faktor yang Mempengaruh Pendapatan Migran Kommuter dari Kelurahan Tanah Mas ke Kota Palembang - Mutmainna Mutmainna; Bambang Bemby Soebyakto; Ridhah Taqwa (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2017)
The research was also to find out the effects of some factors on the migrants commuter (study cases of the retail trade from Tanah Mas Village to Palembang City). This Research have done in Tanah Mas Village with 398 populations. From this populations, was taken the samples as many 100 commuter migrants, where the technique of collecting the sample was proportional stratified random sampling . To analyze the data was used multiple linear regression methods this analysis was used to find how the marital status, number of family members, working duration, transportation type, traders of type, and motivation traders influence the income commuter migrants. The results of the research is simultaneously, variable of the marital status, number of family members, working duration, transportation type, traders of type, and motivation traders influence significantly on the income commuter migrants in Tanah Mas Village to Palembang City. Partially, number of family members, transportation type, and traders of type influence significantly on the income commuter migrants, while the marital status, working duration, and motivation traders not significantly income commuter migrants in Tanah Mas Village to Palembang City